Risk factors and co-morbidity of skin disorders among female schoolchildren in eastern Saudi Arabia. - Al-Saeed, Wafa Y; AL-Dawood, Kasim M; Bukhari, Igbal A; Bahnassy, Ahmed A (Investigación Clínica, 2009)
The aim of this study was to determine the risk factors of skin disorders among female schoolchildren in primary and intermediate schools in Al-khobar city, Eastern Saudi Arabia. This is a cross-sectional study conducted in Al-Khobar city during the period of January to March 2003. It involved 2239 female schoolchildren randomly selected from 30 regular public and private primary and preparatory schools. A multi-stage stratified random sampling technique with proportional allocation was used. Data was collected using a pre-designed structured questionnaire and clinical examination. Dandruff was negatively associated with private schools and positively associated with age, body mass index and overcrowding. The association of atopic dermatitis with family history of atopy and bronchial asthma was documented in this study. Those who were at high risk of getting acne were schoolchildren who had more baths per week and lived in villas with a high number of rooms (in other words the high socioeconomic class). Pediculosis had a negative association with a high level of father education and high socioeconomic status and a positive association with living in a flat and the number of siblings. It was concluded that sex, socioeconomic status, family history, parents”™ education, home type, and overcrowding were found to be risk factors for some skin disorders. Accordingly, it is recommended that a preventive health education program for schoolchildren with different levels of skin diseases be started considering the predictive variables that increase the prevalence of these diseases.